1987
DOI: 10.1111/j.1365-2362.1987.tb01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the peritoneal transport of water and solutes during peritonitis in continuous ambulatory peritoneal dialysis patients

Abstract: The in situ intraperitoneal volume and the mass transfer area coefficients (MTC) of urea, lactate, creatinine, glucose, kanamycin, inulin, beta 2-microglobulin, albumin and IgG were studied in eight continuous ambulatory peritoneal dialysis (CAPD) patients. All patients were studied during a 4-h dialysis dwell, first during peritonitis and subsequently after recovery from the infection. The maximal intraperitoneal volume was reached at 68 min during peritonitis and at 150 min in the study after recovery (P les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 23 publications
4
87
0
2
Order By: Relevance
“…As compared with controls, mice with peritonitis showed cloudy dialysates with positive cultures and high WBC counts in the dialysate with a majority of polymorphonuclear leukocytes at day 1 followed by a progressive increase in macrophages and lymphocytes; mononuclear cells infiltrates and vascular proliferation in the peritoneum at day 7 ( Figures 3 through 5); upregulation of eNOS and iNOS ( Figures 4 and 6); increased permeability for urea and glucose, with a loss of sodium sieving ( Figure 2); and a combination of decreased UF and increased protein loss in the dialysate (Table 3). These changes, which confirm our previous observations in rat models (6,14), are characteristic of acute peritonitis in PD patients (5). These functional and structural studies thus demonstrate the relevance of the mouse as a model for studying peritoneal transport at baseline and during acute peritonitis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As compared with controls, mice with peritonitis showed cloudy dialysates with positive cultures and high WBC counts in the dialysate with a majority of polymorphonuclear leukocytes at day 1 followed by a progressive increase in macrophages and lymphocytes; mononuclear cells infiltrates and vascular proliferation in the peritoneum at day 7 ( Figures 3 through 5); upregulation of eNOS and iNOS ( Figures 4 and 6); increased permeability for urea and glucose, with a loss of sodium sieving ( Figure 2); and a combination of decreased UF and increased protein loss in the dialysate (Table 3). These changes, which confirm our previous observations in rat models (6,14), are characteristic of acute peritonitis in PD patients (5). These functional and structural studies thus demonstrate the relevance of the mouse as a model for studying peritoneal transport at baseline and during acute peritonitis.…”
Section: Discussionsupporting
confidence: 77%
“…The capillary endothelium, which expresses both the endothelial nitric oxide (NO) synthase (eNOS) and the water channel aquaporin-1 (AQP1), constitutes the major barrier for solutes and water transport during PD (3,4). Acute peritonitis is characterized by an increased EPSA, with increased permeability for small solutes and glucose, a faster-than-normal dissipation of the osmotic gradient, a decrease of free-water permeability, and a loss of ultrafiltration (UF) (5,6). These modifications are associated with mononuclear cell infiltrate and vascular proliferation within the PM (6).…”
mentioning
confidence: 99%
“…The small-solute transport seen with HPG solutions, measured as the D/P ratio of urea, was similar to that with PDS. The latter finding supports the biocompatibility of HPG, given that increased solute transport may have suggested the increased vascular permeability that occurs in acute peritoneal inflammation (32,33). Moreover, urea clearance values for HPG appear to follow the UF profiles observed in our experiments.…”
Section: Discussionsupporting
confidence: 55%
“…In contrast, some authors found no association between the occurrence of peritonitis and peritoneal transport status (14)(15)(16) when peritonitis was treated properly (15) or adjustments for time on PD were made (16). Studies investigating the effects of a single, but not the first, peritonitis episode reported equivocal results (8,9,11,(17)(18)(19).…”
Section: Pdimentioning
confidence: 99%
“…35,NO. 3 FIRST PERITONITIS ALTERS THE NATURAL COURSE OF PERITONEAL TRANSPORT temporary effect of peritonitis on small solute transport and net ultrafiltration, which recovered after the acute phase (8,9). Others identified a sustained effect of recurrent or severe peritonitis on peritoneal transport characteristics (10)(11)(12)(13).…”
Section: Pdimentioning
confidence: 99%